Symphony and Maintenance of Seized Ships: Experimenting U.S Maritime Court’s Practice in Nigeria - Abdulrazaq Owolabi Abdulkadir; Saheedat Owolabi Lawal (Universitas Lampung, 2023)
Maintaining and managing a seized ship is an important aspect of the Maritime Industry globally. In countries like the United States, measures have been put in place to ensure that when ships are seized in lieu of a maritime proceeding, such ships are adequately managed and maintained for that period. In contrast, when a ship is seized in Nigeria, there is little to no guarantee that the vessel will be maintained efficiently by the body responsible for its management. It is therefore essential to investigate the reason for such lack of guarantee and how it can be solved to improve the state of affairs in the country’s maritime sector. This research adopted a doctrinal method of research through analysis of statutory provisions as well as cases to use the power of reasoning to collect data from the use of Law textbooks, articles in journals, and various online resources. This paper aims to is to discuss the instances where states can seize ships, the procedure of arrest in Nigeria, forfeiture of ships and make a comparison to the procedure adopted in the Maritime Sector of the U.S, the challenges faced by the Nigerian Maritime Sector and recommendations on how ships can be better maintained through the establishment of Maritime or Admiralty Court and the posting of a bond by the owner of a seized ship for its release pending the determination of the maritime proceedings in court as practice in the US.